2014
DOI: 10.1128/jvi.00652-14
|View full text |Cite
|
Sign up to set email alerts
|

Role of the C Terminus of Lassa Virus L Protein in Viral mRNA Synthesis

Abstract: The N terminus of arenavirus L protein contains an endonuclease presumably involved in "cap snatching." Here, we employed the Lassa virus replicon system to map other L protein sites that might be involved in this mechanism. Residues Phe-1979, Arg-2018, Phe-2071, Asp-2106, Trp-2173, Tyr-2179, Arg-2200, and Arg-2204 were important for viral mRNA synthesis but dispensable for genome replication. Thus, the C terminus of L protein is involved in the mRNA synthesis process, potentially by mediating cap binding. L a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 32 publications
0
37
0
Order By: Relevance
“…The cap-binding function might have been lost during arenavirus evolution, while the domain might have gained or maintained other functions in virus transcription [13]. A similar situation was proposed for Thogoto virus, an insect transmitted orthomyxovirus.…”
Section: Discussionmentioning
confidence: 96%
“…The cap-binding function might have been lost during arenavirus evolution, while the domain might have gained or maintained other functions in virus transcription [13]. A similar situation was proposed for Thogoto virus, an insect transmitted orthomyxovirus.…”
Section: Discussionmentioning
confidence: 96%
“…5, see below) of negative strand RNA viruses (NSVs), whereas the N-and C-terminal parts did not exhibit clear protein signatures including RNA helicases or methyltransferases involved in RNA capping (Vieth et al, 2004). Mutation-function studies of the LASV L protein showed that residues critical for function were located both within and outside the predicted polymerase domain and identified specific amino acid residues that were required for RNA transcription, but not replication, mediated by the LASV polymerase in cell-based minigenome (MG) assays (Hass et al, 2008;Lehmann et al, 2014;Lelke et al, 2010). Interestingly, mutations of evolutionary conserved acidic (Asp and Glu) and basic (Lys and Arg) residues within the LASV L protein identified residues that played a critical role in mRNA synthesis without significantly affecting RNA replication .…”
Section: Arenavirusesmentioning
confidence: 99%
“…Site numbering refers to Lassa virus ( LASV ) strain AV (Accession ID s: S segment, AF 246121; L segment, AY 179171). In the alignment, few representative OW arenaviruses are shown; conserved sites that affect protein function are in red (Lehmann et al., ), and positively selected sites are highlighted in yellow. SP , Signal Peptide…”
Section: Resultsmentioning
confidence: 99%
“…Even though the L protein plays a central role in viral genome replication and transcription, structural and functional information is more limited compared to NP. The N‐terminal domain of L has endonuclease activity (Shao, Liang, & Ly, ), which presumably cleaves off the cap structure (Lehmann et al., ). Three of the positively selected sites (S64, E124 and Q125) are located in close spatial proximity to the active site (Figure a).…”
Section: Resultsmentioning
confidence: 99%